Pengaruh Asosiasi Merek Terhadap Keputusan Pembelian Dengan Kesadaran Merek Sebagai Variabel Intervening - Arini Wahyunina Putri; Asep Muhammad Ramdhan; R Deni Muhammad Danial (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The research was aimed at determining the influence of brand awareness in mediating the relationship between brand associations toward buying decision. The research methods applied were associative descriptive and cluster sampling method by spreading out online questionnaires to 385 students who were Oppo users in Sukabumi city. The technique of analyzing data used in the research was Structural Equation Modeling (SEM) with the help of data tabulating software IBM SPSS AMOS 24. The results of the research show that brand association influence significantly toward brand awareness, brand awareness influences positively and significantly toward buying decision, and brand awareness mediates the relationship of brand awareness toward buying decision. Keywords: Brand Association, Brand Awareness, Buying Decision